Too much water? Not enough? In situ monitoring of the mechanochemical reaction of copper salts with dicyandiamide. Issue 6 (21st January 2022) - Casali, Lucia; Feiler, Torvid; Heilmann, Maria; Braga, Dario; Emmerling, Franziska; Grepioni, Fabrizia
Abstract : In situ monitoring, via X-ray and Raman spectroscopy, of mechanochemical reactions between dicyandiamide and copper(ii ) salts shows that the amount of added water and the milling frequency strongly impact on the products of the solid state synthesis. Abstract : In situ monitoring of mechanochemical reactions between dicyandiamide (DCD) and CuX2 salts (X = Cl −, NO3 − ), for the preparation of compounds of agrochemical interest, showed the appearance of a number of phases. It is demonstrated that milling conditions, such as the amount of water added in wet grinding and/or the milling frequency, may affect the course of the mechanochemical reactions, and drive the reaction towards the formation of different products. It has been possible to discover by in situ monitored experiments two novel crystalline forms, namely the neutral complexes [Cu(DCD)2 (OH2 )2 (NO3 )2 ] (2 ) and [Cu(DCD)2 (OH2 )Cl2 ]·H2 O (4 ), in addition to the previously known molecular salt [Cu(DCD)2 (OH2 )2 ][NO3 ]2 ·2H2 O (1, DIVWAG) and neutral complex [Cu(DCD)2 (OH2 )Cl2 ] (3, AQCYCU), for which no synthesis conditions were available. Compounds 2 and 4 were fully characterized via a combination of solid-state techniques, including X-ray diffraction, Raman spectroscopy and TGA.